Legal review of the protection of business actors in bankruptcy cases (Decision No. 28 / Rev.Sus-bankruptcy/2017 / PN Jkt.Pst)": Legal review of the protection of business actors in bankruptcy cases (Decision No. 28 / Rev.Sus-bankruptcy/2017 / PN Jkt.Pst)" - Aisyah Aisyah; Dedi Yusuf Kristian Gultom; Felim yenson (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study discusses related to consumer protection when business actors are based on the Commercial Court decision decision Number No.28 / Rev.Sus-bankruptcy/2017/PN Pn.Jkt.Pst is caused by not being able to meet its debt obligations in accordance with the terms of bankruptcy under Article 2 Paragraph (1) of Law No. 37 of 2004 concerning bankruptcy and postponement of debt repayment obligations. The purpose of this study to determine the legal remedies that consumers can do and the liability of the company manager if the company is declared bankrupt due to errors or omissions. This research method uses the type of Normative research by using the method of statutory approach (statue approach), in which researchers examine further from the side of the applicable legislation. The method of data collection used is a literature study, analyzing the legal material obtained, which is in accordance with the problem and the purpose of the study. The results showed that bankruptcy brings significant consequences for the debtor, especially in terms of loss of control over its assets and the transfer of responsibility to the curator. This shows the importance of the curator's role in maintaining the value of the bankrupt's assets and protecting the interests of all related parties. We are of the opinion that there is a need for increased understanding and socialization of the rights and obligations of debtors and bankruptcy procedures so that business actors can be better prepared to face difficult situations. In addition, the government needs to consider policies that are more supportive of post-bankruptcy business recovery, so that business actors have the opportunity to bounce back and contribute to the national economy.